Grassland and globalization – challenges for north‐west European grass and forage research. (12th April 2013) - Taube, F.; Gierus, M.; Hermann, A.; Loges, R.; Schönbach, P.
Abstract The concept of sustainable intensification has recently been developed to raise productivity (as distinct from increasing volume of production) while reducing environmental impacts. This means increasing yields per unit of inputs (including nutrients, water, energy capital and land) as well as per unit of undesirable outputs (such as greenhouse gas emissions, water pollution or loss of biodiversity). It is thus helpful to understand 'intensification' as referring to 'environmental factor productivity' or 'eco‐efficiency'. Worldwide, grassland is the most important agroecosystem delivering ecosystem services ranging from feed supply for ruminants and soil carbon storage to habitats of biodiversity. However, worldwide, grassland is under threat due to intensified land use and land‐use changes from grass to arable. In this article, we (i) highlight ecosystem services of selected grassland biomes abroad of Europe, (ii) show evidence of sustainable as well as non‐sustainable intensification options in these grassland biomes linked to European agriculture by exports of agricultural commodities (e.g. soy) and (iii) derive research strategies for north‐west European grassland research and management to match sustainable intensification strategies for the grassland‐based dairy industry.